Parsifal: Story and Analysis of Wagner's Great Opera - Haweis, H. R. (Hugh Reginald), 1839-1901 (Salt Lake City, UT : Project Gutenberg, 2007)
"Parsifal: Story and Analysis of Wagner's Great Opera" by H. R. Haweis is a comprehensive exploration of Wagner's renowned opera, published in the early 20th century. This book falls into the category of a musical analysis and commentary, offering insights into the themes, characters, and narrative of the opera. The author, H. R. Haweis, seeks to unravel the layers of meaning within "Parsifal," discussing its deep connections to religious symbolism and the human experience, making it an intriguing read for opera enthusiasts and those interested in musical literature. The book provides a detailed analysis of the opera's three acts, portraying the journey of Parsifal, the "guileless one," who becomes embroiled in the mystical world of the Grail and the struggle between good and evil. Haweis introduces significant characters such as Amfortas, the wounded king, and Kundry, who embodies the conflict of desire and redemption. As Parsifal confronts the sorcerer Klingsor and ultimately grasps his role in healing Amfortas, the narrative unfolds themes of sacrifice, purity, and spiritual awakening. Through vivid descriptions and emotional depth, Haweis effectively captures the essence of Wagner's work, inviting readers to appreciate its philosophical and artistic grandeur. (This is an automatically generated summary.)
Release date is 2007-01-04
E-text prepared by David Newman, V. L. Simpson, Chuck Greif, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Operas -- Stories, plots, etc; Wagner, Richard, 1813-1883. Parsifal; Perceval (Legendary character) -- Drama